Guidelines for Proper Reporting of Clinical Significance, Including Minimal Clinically Important Difference, Patient Acceptable Symptomatic State, Substantial Clinical Benefit, and Maximal Outcome Improvement - Harris, Joshua D; Brand, Jefferson C; Cote, Mark; Waterman, Brian; Dhawan, Aman (Arthroscopy, 2023)
Patient-reported outcome measures (PROM) need to be responsive, reliable, and validated for the specific condition or treatment. PROMs also need to exhibit a dose-dependent response across a diverse patient population, unlimited by floor and ceiling effects. Statistically significant differences between compared groups might not always represent clinically important differences. Measures of clinical significance reflect a spectrum of patient satisfaction after an intervention. A noticeable difference to the patient is assessed with minimal clinically important difference (MCID), patient satisfaction by patient acceptable symptomatic state (PASS), and a "considerable" improvement by substantial clinical benefit (SCB). Clinical relevance measured by these clinically significant outcomes (CSO) are limited by ceiling effects. Maximal outcome improvement (MOI) might more accurately account for patients with higher baseline or preoperative PROMs, thereby limiting ceiling effects. The acts of measuring (and reporting) patient-centered endpoints may actually be of greater importance than collecting objective clinician-measured data. As the old surgeon's aphorism goes, "nothing ruins good results like good follow-up."